Diagnostic Reliability, Accuracy and Safety of Ultrasound-guided Biopsy and Ascites Puncture in Primarily Inoperable Ovarian Tumours - Vlasak, Pavel; Bouda, Jiri; Kostun, Jan; Berezovskiy, Denis; Zikan, Michal; Weinberger, Vit; Ondic, Ondrej; Rusavy, Zdenek; Kucera, Radek; Topolcan, Ondrej; Novotny, Zdenek; Presl, Jiri (Anticancer research, 2020)
BACKGROUND/AIM: To compare the diagnostic reliability, accuracy and safety of ultrasound-guided biopsy (Tru-Cut biopsy) and ascites puncture in patients with a primarily inoperable malignant ovarian tumor. PATIENTS AND METHODS: This is a retrospective analysis of the studied methods in consecutively examined patients and a prospective validation of these methods. 79 women with a suspected primarily inoperable ovarian tumor underwent Tru-Cut biopsies and were included in the ultrasound-guided biopsy group. In addition, 55 patients after ascites puncture were enrolled in the comparison group. Both procedures were performed in 48 patients for the prospective validation. RESULTS: Significant differences in favour of ultrasound-guided biopsy were found in all studied variables (malignancy confirmation 72.9% vs. 95.8%, tumor origin 52.1% vs. 89.6%, histologic subtype 43.8% vs. 85.4% and accuracy, i.e. agreement of preoperative and definitive diagnosis 43.7% vs. 95.4%). CONCLUSION: Ultrasound-guided biopsy is an accurate, reliable, safe and minimally invasive method. Owing to the high reliability and accuracy, it has the capacity to replace ascites puncture with cytologic examination or a more invasive method (laparoscopy, laparotomy) for adequate tumor sampling.
Keywords: Female; ascites; Punctures; punkce; Image-Guided Biopsy; reprodukovatelnost výsledků; Retrospective Studies; Ovarian Neoplasms; Histocytochemistry; cytodiagnostika; retrospektivní studie; Humans; Ultrasonography; histocytochemie; nádory vaječníků; lidé; Cytodiagnosis; Ascites; ultrasonografie; Reproducibility of Results; ultrazvukem navigovaná biopsie; ženské pohlaví